PELATIHAN BISNIS ONLINE KARANG TARUNA LINGKUNGAN RW 013 KELURAHAN PANINGGILAN UTARA KECAMATAN CILEDUG KOTA TANGERANG - Setiawan, Rahmad; Darmadi, Darmadi; Suhartono, Agus; Halomoan, Yan Kristian (LPPM Universitas Pamulang, 2020)
This community service activity aims to transfer knowledge on how to maximize operationalization and become a member of the media. Open stalls and Online Business Training in order to increase sales of products and services offered by utilizing open stall applications. The method used is in the form of presentation of material in the form of presentation theory and practice to become a member and market the product. The method of activity used is in collaboration with Karang Taruna and looking for problems in the place so that it can provide the right solution in motivating members who are business people in Karang Taruna. After the analysis, we provide training in the form of materials and practices that aim to develop the ability to increase marketing via bukalapak media (online) for members of Karang Taruna Lingkungan The results of the activity showed that prior to the implementation of the PKM, the members of Karang Taruna Lingkungan were not familiar with the terms related to product marketing via online media, but after the implementation of the activities the Karang Karanguna can understand the basics of operating and becoming a member of the media. Open simple stalls. PKM activities play a positive role in increasing the knowledge and skills of participants in creating an Online Business account.